2015
DOI: 10.7567/jjap.54.04dl10
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic signal imaging of brain function using a small implantable CMOS imaging device

Abstract: A brain functional imaging technique over a long period is important to understand brain functions related to animal behavior. We have developed a small implantable CMOS imaging device for measuring brain activity in freely moving animals. This device is composed of a CMOS image sensor chip and LEDs for illumination. In this study, we demonstrated intrinsic signal imaging of blood flow using the device with a green LED light source at a peak wavelength of 535 nm, which corresponds to one of the absorption spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The velocities were 0.88 mm/s, 1.13 mm/s, and 1.22 mm/s. w was difficult [10,11] This device could simultaneously measure the blood-flow velocity and brain activity. These results suggested that the chronic brain blood-flow imaging device could be used for the development of a therapeutic methods for cerebrovascular disease [21].…”
Section: Conditions Of the Mouse Cerebral Surface With The Chronic Rementioning
confidence: 99%
See 1 more Smart Citation
“…The velocities were 0.88 mm/s, 1.13 mm/s, and 1.22 mm/s. w was difficult [10,11] This device could simultaneously measure the blood-flow velocity and brain activity. These results suggested that the chronic brain blood-flow imaging device could be used for the development of a therapeutic methods for cerebrovascular disease [21].…”
Section: Conditions Of the Mouse Cerebral Surface With The Chronic Rementioning
confidence: 99%
“…In long-term experiments, the implanted device moved in the brain, and the imaging area was obstructed. Additionally, these devices [10,11] did not observe brain-surface images for a long time, because the structures of the devices damaged the brain surface. In this study, a blood-flow imaging device was developed for long-term and repeated behavioral experiments with the same small experimental animal.…”
Section: Introductionmentioning
confidence: 99%
“…The required equipment obstructs the animals' natural behavior. An implantable optical imaging device based on complementarymetal-oxide-semiconductor (CMOS) technology is an alternative approach to observe neural activities while moving freely (Ohta et al, 2009(Ohta et al, , 2017Haruta et al, 2015;Takehara et al, 2015). Previously, our group has reported implantable CMOS image sensors for contact imaging, which are ultra-small and lightweight.…”
Section: Introductionmentioning
confidence: 99%
“…MicroLED arrays have been studied for use in other biomedical applications including optogenetic stimulation. [25][26][27] The ORIS device designed and fabricated in this work extends the technology to the application of seizure monitoring using a novel bi-directional configuration on a flexible polyimide substrate capable of localizing spatiotemporal effects of seizures on CBV.…”
Section: Introductionmentioning
confidence: 99%